Large interstitial del(13)(q13q14.3): the importance of detailed clinical information in cytogenetic studies - Oliveira, Fernanda Paula (2012)
Interstitial deletions of chromosome 13 are known to be associated with retinoblastoma. A wider syndrome may accompany the deletion, including mental retardation and craniofacial dysmorphism. The severity of the phenotype depends on the extent of the deletion. Retinoblastoma is a malignant tumor in the retina and is the most common ocular cancer in children. The association of most cases of retinoblastoma with an interstitial del(13q) has led to the localization of the retinoblastoma gene in 13q14. We report a case of a boy aged 8 referred for cytogenetic studies, presenting with mild mental retardation, craniofacial dysmorphism, delayed intrauterine growth (IUGR) and retinoblastoma. The karyotype was obtained from peripheral blood lymphocyte cultures using high-resolution GTG banding and standard techniques. Fluorescence in situ hybridization was performed using the LSI 13 (RB1) probe (Vysis) for region 13q14 spanning the RB1 gene. The chromosomal analysis revealed a large interstitial deletion of the long arm of chromosome 13. Although the exact breakpoints were difficult to establish, the deleted region did not appear to encompass the band which includes the retinoblastoma gene. Molecular cytogenetic techniques showed that the retinoblastoma gene was deleted. This confirmed the clinical indication of retinoblastoma and defined the deletion breakpoints more precisely. Final karyotype: 46,XY,del(13)(q13q14.3).ish del(13) (q14.1q14.3)(RB1−). Except for the presence of IUGR, the clinical description of this patient is in agreement with other reports in the literature. We would like to emphasize the importance of detailed clinical information that, together with classical and molecular cytogenetic techniques, could be useful in better defining the breakpoints, establishing correct genotype/phenotype correlation and thus providing appropriate genetic counselling. The blood samples of the parents were requested for karyotype analysis in order to clarify this chromosome deletion.